Comparing the Efficacy of the Total Stabilizing and Posterior Stabilizing Knee Prostheses in Obese and Preobese Females: A Retrospective Cohort Study - Worhacz, Kellen; Jacofsky, Marc C.; Jacofsky, David J.; Ahmed, Sarim (The Journal of Knee Surgery, 2018)
Obesity is associated with increased surgical complications that may lead to suboptimal total knee arthroplasty (TKA) outcomes. Additionally, females exhibit increased rates of severe, clinical osteoarthritis OA, along with increased ligamentous laxity. Therefore, obese females present a particularly challenging case for TKA with increased joint loads coupled with a propensity for instability. This study retrospectively analyzed knee range of motion and stability of one TKA designs with two different degrees of polyethylene conformity in the obese female population. The implants (Stryker Triathlon total stabilizing [TS] and Stryker Triathlon posterior stabilizing [PS]) differ in their level of constraint, with the TS being more constrained. We hypothesized that the TS implants would be associated with improved functional outcomes in the obese female population, secondary to increased coronal stability to offset the ligamentous laxity. Of 482 knees reviewed, 173 met the inclusion criteria of: female, body mass index (BMI) ≥ 25, receiving TS (N = 93), or PS (N = 8). Primary knee outcome measures were: active flexion, passive flexion, active extension, passive extension, and stability at 0° and 30° flexion. These factors were statistically analyzed at preop, 2-week, 6-week, 3-month, and 1-year time points. Preoperatively, the TS cohort was significantly higher in BMI and knee laxity, potentially starting this cohort at a functional disadvantage. Postoperatively, the TS implant was associated with a statistically significant early improvement in active and passive knee extension. There was no longer any significant difference in knee laxity postop. Our data support the hypothesis that obese females may benefit from the increased stability afforded by the TS design.
Keywords: arthroplasty; constraint; knee; obesity